Karl Marx architect for the 20th century - Dominguez, Fernanda; Garcia, Pablo; Films for the Humanities and Sciences (New Jersey : Films for the Humanities & Sciences, 2006)
This program chronicles Marx's life and intellectual development, including the publication and impact of his major writings. Beginning with his birth and religiously confused childhood in Prussia, the video traces Marx's student years and his early affinity for Hegel, outlines his radicalization in Paris and Brussels, and describes his friendship and partnership with Friedrich Engels
Title from title screen
Executive producers, Paul Iacono, Camila O'Donnell
Narrator: Liz Chang
DVD format
Keywords: Marx, Karl, -- 1818-1883; Communists -- Biography